CMP slurry composition for polishing copper barrier layer
By using specific proportional additives in the CMP slurry composition and adjusting the particle size of colloidal silica, the problems of poor polishing amount, corrosion and depression in the prior art are solved, and high-efficiency polishing and low defect count are achieved effect.
Patent Information
- Application Number
- CN202380051638.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-06
- Filing Date
- 2023-06-21
- Publication Date
- 2025-02-18
AI Technical Summary
When polishing the copper barrier layer, the existing CMP slurry composition has poor polishing amount, corrosion problems, difficulty in layer flattening, and depression.
CMP slurry compositions including colloidal silica, heterocyclic compounds, organic acids, surface protectors, nitrides, pH adjusters and deionized water are used to adjust the content of additives and solvents, and to adjust the colloidal dioxide. The particle size of silicon is used to optimize the polishing selection ratio and polishing rate.
The step difference removal efficiency between the silicon oxide film and the copper film layer is significantly improved, the number of depressions, corrosion and defects is reduced, and the reliability and performance of the polished semiconductor equipment layer is improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to a CMP slurry composition for polishing a copper barrier layer, which is used for chemical mechanical planarizing (CMP) of tantalum nitride or tantalum used as a diffusion barrier film in the presence of interconnection structures in an integrated circuit device. The CMP slurry composition provided by the present invention is an effective composition comprising abrasive particles, a heterocyclic compound, an organic acid, a surface protective agent, a nitride, a pH regulator, and a balance of deionized water, and can provide an excellent CMP slurry composition, which has excellent dispersibility and stability of abrasive particles, a high polishing selectivity, and less dishing and defects than the CMP slurry composition according to the prior art. Background Art
[0002] Recently, with the development of semiconductor manufacturing process technology, the semiconductor industry has increasingly relied on copper electronic interconnects to form integrated circuits. These copper interconnects have low resistivity and excellent electromigration properties.
[0003] Since copper has many advantages in terms of efficiency, such as excellent electromigration characteristics and low resistance, it has been mainly used as a finite electrical connection material for semiconductor integrated circuits such as ULSI, which are becoming increasingly fine and highly integrated.
[0004] However, due to the limitation that copper cannot be used for integrated circuits due to the difficulty in patterning based on dry etching, a method of forming copper interconnects by a CMP process based on a dual damascene process has been proposed to overcome this problem. In the CMP process, copper is formed into a Cu 2+ layer containing ions as copper oxide. + or Cu 2+ A porous oxide film layer composed of CuO, CuO2, Cu(OH)3, etc.
[0005] However, copper is relatively soft compared to other materials such as tetraethoxysilane (TEOS) or tungsten, and is more susceptible to electrochemical corrosion than tungsten. Therefore, although the polishing rate is high, it is easy to cause dishing or erosion caused by over-polishing and scratches. In particular, the components of the polishing slurry and foreign matter such as oxides generated during the polishing process penetrate into the copper oxide film layer through the pores of the porous film. Such a phenomenon may cause problems in the next process, that is, the photolithography process, etc., especially in the case of highly integrated circuits composed of 6 to 7 layers or more according to the wiring design, since the performance of the circuit varies depending on the flatness of each layer, it may become a fatal defect.
[0006] Copper is very corrosive in many dielectric materials such as silicon dioxide and low-k or doped versions of silicon dioxide, so a diffusion barrier layer is necessary to prevent copper from diffusing into the underlying dielectric material.
[0007] Typical barrier materials include tantalum, tantalum nitride, tantalum silicon nitride, titanium, titanium nitride, titanium silicon nitride, titanium-titanium nitride, titanium-tungsten, tungsten, tungsten nitride, and tungsten silicon nitride.
[0008] In response to the increasing demand for high-density integrated circuits, manufacturers are currently assembling integrated circuits that include multiple overlying layers of metal interconnect structures. During the assembly of the device, simply flattening the interconnect layer can improve packaging density, process uniformity, and production quality, and most importantly, allow chip manufacturers to assemble multiple layers of integrated circuits. As a relatively effective method for producing a flat surface, chip manufacturers rely on chemical mechanical polishing (CMP).
[0009] The CMP process is typically performed in two stages. First, the polishing process uses a "stage 1" slurry designed to rapidly remove copper.
[0010] After the initial copper removal, a "stage 2" slurry removes the barrier material. Stage 2 slurries are typically required to have excellent selectivity in removing barrier materials without adversely affecting the physical structure or electrical properties of the interconnect structure. Since alkaline polishing slurries traditionally have much faster Ta / TaN removal rates than acidic slurries, commercial stage 2 slurries typically have an alkaline to neutral pH. Another factor that emphasizes the advantages of barrier metal polishing slurries having a neutral to alkaline pH involves the necessity of preserving the metal overlying the barrier metal during the stage 2 polishing process. In order to reduce dishing of the metal interconnect, the metal removal rate must be very low.
[0011] Therefore, in the chemical mechanical polishing method, such a barrier slurry composition needs to have a high barrier removal rate, very low post-polishing topography, no corrosion defects, and very low scratches or corrosion. Depending on which polishing agent, oxidizing agent or additive is selected, the variation range of important variables in the semiconductor process such as surface flaws, surface roughness, surface defects, erosion and corrosion after polishing can be minimized, and the metal insulating film or diffusion wall or metal layer can be polished effectively using the target polishing ratio.
[0012] Experiments using CMP slurry compositions according to the prior art have shown that there are problems with CMP work throughput due to poor polishing of copper and tantalum, problems with reduced equipment performance and product yield due to corrosion of copper materials, problems with layer flattening, and problems with pitting during polishing. In addition, in the case of a process for polishing a copper film, it is necessary to achieve a low level of surface defects at an appropriate polishing rate, but the CMP slurry compositions according to the prior art have problems such as a prolonged polishing process time or the appearance of surface defects.
[0013] (Prior art literature)
[0014] (Patent Document 1) Korean Patent Registration No. 10-1465604;
[0015] (Patent Document 2) Korean Patent Registration No. 10-1548715;
[0016] (Patent Document 3) Korean Patent Registration No. 10-1698490;
[0017] (Patent Document 4) Korean Patent Publication No. 10-2021-0095548. Summary of the invention
[0018] Technical issues
[0019] The object of the present invention is to solve the following problems existing in the CMP slurry composition according to the prior art: the problem of CMP work processing volume caused by poor polishing of copper and tantalum, the problem of reduced equipment performance and product yield caused by corrosion of copper substances, the problem of layer flattening, and the pitting phenomenon caused by polishing.
[0020] Furthermore, the present invention aims to provide a CMP slurry composition for polishing a copper barrier layer, which has an appropriate polishing rate and significantly reduces dishing, corrosion, and defects in the process of polishing a copper film compared to existing slurries.
[0021] Furthermore, an object of the present invention is to provide a CMP slurry composition for polishing a copper barrier layer, which has a greater step difference removal rate of a silicon oxide film and a copper film than that of a conventional slurry in terms of solving the above-mentioned problems generated in the copper CMP process.
[0022] Technical means
[0023] In order to achieve the above object, the present invention provides a CMP slurry composition for polishing a copper barrier layer, comprising: abrasive particles consisting of colloidal silica, a heterocyclic compound, an organic acid, a surface protective agent, a nitride, a pH regulator, and a balance of deionized water. By adjusting the content of the additives and the solvent and adjusting the particle size of the colloidal silica, the polishing selectivity and the polishing rate relative to the silicon oxide film, the tantalum film and the copper film are adjusted to perform polishing.
[0024] In a preferred embodiment of the present invention, the particle size of the colloidal silica may be 75 to 95 nm.
[0025] In a preferred embodiment of the present invention, the heterocyclic compound has two or more nitrogen atoms and may include one or more selected from the group consisting of 1,2,4H-triazole, 5-methylbenzotriazole, tetrazole, imidazole, 1,2-dimethylimidazole, benzotriazole (BTA), 1H-benzotriazole acetonitrile, and piperidine.
[0026] In a preferred embodiment of the present invention, the surface protective agent may include: a nonionic surface protective agent selected from polyvinyl alcohol (PVA), ethylene glycol (EG), glycerol, polyethylene glycol (PEG), polypropylene glycol (PPG), or polyvinyl pyrrolidone (PVP); and an anionic surface protective agent selected from ammonium dodecyl benzene sulfonate, ammonium polyoxyethylene alkyl sulfonate, ammonium polyoxyethylene alkyl aryl sulfonate, etc.; two or more selected from these surface protective agents may also be used in combination. It is best to use a nonionic polyvinyl pyrrolidone (PVP) and anionic ammonium dodecyl benzene sulfonate in combination.
[0027] In a preferred embodiment of the present invention, the organic acid may include any one selected from the group consisting of citric acid, glutaric acid, malic acid, maleic acid, oxalic acid, phthalic acid, succinic acid, tartaric acid, and acetic acid; and may also include any one selected from the group consisting of nitrilotriacetic acid (NTA), iminodiacetic acid (IDA), methyliminodiacetic acid (MIDA), hydroxyethyliminodiacetic acid (HIDA), diethylenetriamine pentaacetic acid (DPTA), ethylenediaminetetraacetic acid (EDTA), N-hydroxyethylethylenediaminetetraacetic acid (N-hydroxyethylethylenediaminetetraacetic acid (N-Hydroxy ... One or more of the amino acid group consisting of 1,2-diamino-2,4-diamino-1,4 ...
[0028] In a preferred embodiment of the present invention, the antioxidant may include one or more selected from the group consisting of ascorbic acid, L(+)-ascorbic acid, isoascorbic acid, ascorbic acid derivatives, gallic acid, formamidinesulfinic acid, uric acid, tartaric acid, and cysteine.
[0029] In a preferred embodiment of the present invention, in order to adjust the pH value range to alkaline, the pH adjuster may include KOH, NH4OH, NaOH, TMAH, TBAH, KNO3, NH4NO3, HNO3, etc., which can be used alone or in combination. Since the pH value is closely related to the particle stability and polishing rate of the slurry, it must be precisely adjusted.
[0030] In a preferred embodiment of the present invention, the CMP slurry composition may include: 13 to 15 wt % of abrasive particles composed of colloidal silica, abrasive particles, heterocyclic compounds, organic acids, surface protective agents, nitrides, pH adjusters, and the balance deionized water relative to the total weight of the composition.
[0031] In a preferred embodiment of the present invention, the CMP slurry composition may have a pH value of 9 to 12.
[0032] In a preferred embodiment of the present invention, the CMP slurry composition can simultaneously polish a film to be polished consisting of two or more selected from a silicon oxide film, a tantalum film, and a copper film.
[0033] In a preferred embodiment of the present invention, in the polishing, the polishing selectivity ratio of the tantalum nitride film (TaN), the silicon oxide film (Silicon oxide), and the copper film (Cu) may be 1:1-4:0.5-1.
[0034] Advantageous technical effects
[0035] The CMP slurry composition for polishing a copper barrier layer according to the present invention exhibits a higher step difference removal efficiency between a silicon oxide film and a copper film layer, thereby improving productivity.
[0036] Furthermore, the CMP slurry composition for polishing the copper barrier layer according to the present invention exhibits the following effects: it is capable of minimizing recesses, corrosion, defects, etc. while polishing the copper film layer, thereby being capable of efficiently forming a copper wiring layer, etc., of a semiconductor device layer with excellent reliability and characteristics, thereby greatly contributing to obtaining high-performance semiconductor devices. DETAILED DESCRIPTION
[0037] Generally, the nomenclature used in this specification is known and commonly used in the technical field to which the present invention belongs. Unless otherwise defined, all technical terms and scientific terms used in this specification have the same meaning as those generally understood by those with ordinary knowledge in the technical field to which the present invention belongs.
[0038] Throughout the present specification, when a certain part is expressed as “comprising” a certain constituent element, unless there is a particular description to the contrary, it means that other constituent elements are not excluded and other constituent elements may be included.
[0039] Typically, in stage 1, after removing the overburden copper, the polished wafer surface has uneven local and global flatness due to the difference in step height at different locations. Low-density features usually have higher copper step heights, while high-density features usually have lower step heights.
[0040] Due to the step difference after stage 1, a stage 2 CMP slurry with selective polishing compared to the removal rate of copper to oxide is highly desirable.
[0041] In the present invention, "selectivity ratio" refers to different removal rates for different substances under the same polishing conditions.
[0042] The barrier slurry preferably provides one or more of the following in the second stage of the CMP process of the wafer after patterning: better removal rate for various types of films, low degree of within wafer non-uniformity (WIW NU), less residue on the polished wafer after the CMP process, and polishing selectivity for various polishing layers.
[0043] Specific featured distortion that is not suitable for semiconductor manufacturing is damage to copper vias or metal channels caused by chemical components interacting with copper vias or metal channels during the CMP process and causing additional corrosion. Therefore, it is very important to use an anti-corrosion agent in the barrier CMP slurry to reduce additional corrosion of copper vias or trenches during the CMP process and reduce defects.
[0044] In the second stage CMP process, the chemical reaction of the barrier CMP composition includes an oxidation reaction caused by an oxidant such as H2O2 used in the CMP slurry. The surface of the metal such as copper, the pipe, via or trench, the barrier material such as Ta is oxidized to a corresponding metal oxide film.
[0045] Generally speaking, copper is oxidized to cuprous oxide or a mixture of cupric oxides, and Ta is oxidized to Ta2O5. By using chelates, ligands or other chemical additives that can chemically bond with copper cations and tantalum cations in the barrier slurry, the dissolution of copper oxide and tantalum oxide can be promoted, thereby improving the removal rate of copper, pipelines, through holes or trenches and barrier layers or barrier films.
[0046] Therefore, the present invention aims to develop a CMP slurry composition, which significantly reduces corrosion or defects generated in the copper CMP process compared to existing slurries, and can quickly polish silicon oxide films, copper films, and tantalum films.
[0047] The slurry for polishing the copper barrier layer according to the present invention comprises: abrasive particles consisting of colloidal silica, a heterocyclic compound, an organic acid, a surface protective agent, a nitride, a pH adjuster, and the balance of deionized water.
[0048] The colloidal silica is a colloidal solution in which nano-sized silica particles are stably dispersed in a solvent without sedimentation. From the perspective of properly maintaining scratches and removal rates, the particle size of the colloidal silica is preferably 75 to 95 nm, more preferably 80 to 90 nm.
[0049] If the particle size of colloidal silica is less than 75 nm, the removal rate relative to the film quality will decrease and the process time will be longer. If it exceeds 95 nm, scratches will easily form, which is not good.
[0050] Preferably, the amount of the colloidal silica is 13 wt % to 15 wt % relative to the total weight of the composition.
[0051] If the amount of colloidal silica is less than 13 wt %, the removal rate is reduced due to insufficient solid content. If the amount exceeds 15 wt %, aggregation occurs due to excessive content, which is not preferred.
[0052] In the CMP slurry composition according to an embodiment of the present invention, the heterocyclic compound has two or more nitrogen atoms and is selected from the group consisting of 1,2,4H-triazole, 5-methylbenzotriazole, tetrazole, imidazole, 1,2-dimethylimidazole, benzotriazole (BTA), 1H-benzotriazole acetonitrile, or piperidine. From the perspective of corrosion inhibition effect, polishing rate, and stability of the slurry composition, the anticorrosive agent may also be 0.005 wt % to 0.5 wt % of the slurry composition.
[0053] If the anticorrosive agent is less than 0.005 wt %, the polishing of the copper film cannot be controlled, which may cause a dishing problem. If the anticorrosive agent exceeds 0.5 wt %, the polishing rate of the copper film decreases, which may cause a residue problem.
[0054] The polishing rate enhancer of tantalum compounds that can be used in the CMP slurry of the present invention includes nitrides used as pH adjusters. Nitrides are substances used in etching solutions for tantalum or titanium compounds and can effectively remove tantalum during CMP polishing.
[0055] As the nitride used in the present invention, potassium nitrate (KNO3), nitric acid (HNO3), ammonium nitrate (NH4NO3), iron nitrate (Fe(NO3)2), and copper nitrate (Cu(NO3)2) etc. can be included, and these nitrides can also be mixed for use. Generally, titanium or tantalum oxide is a relatively stable substance, which is easily etched by a mixture of hydrofluoric acid and nitric acid, and has the characteristics of slow reaction to alkalinity and aqua regia. Generally, the amount of nitride used in the slurry is preferably in the range of about 0.05 to 10% by weight, and more preferably in the range of about 0.1 to 1% by weight.
[0056] The surface protective agent used in the present invention may include: a nonionic surface protective agent selected from polyvinyl alcohol (PVA), ethylene glycol (EG), glycerol, polyethylene glycol (PEG), polypropylene glycol (PPG), or polyvinyl pyrrolidone (PVP); and an anionic surface protective agent selected from ammonium dodecyl benzene sulfonate, ammonium polyoxyethylene alkyl sulfonate, ammoniumpolyoxyethylene alkyl aryl sulfonate, etc.; two or more selected from these surface protective agents may also be used in combination. It is best to use a nonionic polyvinyl pyrrolidone (PVP) and an anionic ammonium dodecyl benzene sulfonate in combination.
[0057] The nonionic protective agent is adsorbed on the surface of the particles in the solution. Since it contains more than one functional group with affinity for the particles, it can be strongly and continuously adsorbed on the surface of the particles, which plays a role in increasing the particle size. Therefore, it can also play a role in appropriately increasing the polishing rate of the silicon oxide film. In addition, the dispersion stability is maintained by the steric repulsion. Therefore, if the content of the protective agent is less than 0.15% by weight relative to the total weight of the composition, the dispersion force is low and the precipitation is very fast, so precipitation will occur when the polishing liquid is transported, so that the polishing material cannot be uniformly supplied. In contrast, if the content of the dispersant exceeds 1.0% by weight relative to the total weight of the composition, a protective agent layer that acts as a buffer is thickly formed around the polishing material particles, making it difficult for the polishing agent surface to contact the surface to be polished, which may cause the polishing rate to be reduced.
[0058] The surface protectant plays a role in protecting the wafer surface from the residue of the polishing pad or the influence of metal residue and organic residue during polishing, so as to reduce the number of wafer defects, and especially plays a role in cleaning various residues on the wafer surface when the anionic ammonium sulfonate derivative is mixed, so as to further improve the number of defects. Generally, preferably, the amount of the surface protectant used in the slurry is in the range of about 0.15 to 1.0 weight %, and most preferably in the range of about 0.3 to 0.8 weight %.
[0059] In order to adjust the copper removal rate relative to the barrier metal removal rate, an organic acid is included in the CMP slurry of the present invention.
[0060] Organic acids inhibit the re-adsorption of oxidized copper oxides to the copper layer as the polished layer through a chelating reaction with copper oxides, thereby increasing the polishing rate of copper and reducing surface defects. By adding an organic acid that is selective for the target metal component to the slurry, the CMP planarization of the dielectric / metal composite structure can be further improved.
[0061] This increases the erosion rate of the metal phase and increases the polishing selectivity of metal to dielectric phase removal, making the planarization process more effective.
[0062] The organic acid that can be used in the present invention includes carboxylic acid organic acids and amino acid organic acids. First, the carboxylic acid organic acid includes one or more selected from the group consisting of citric acid, glutaric acid, malic acid, maleic acid, oxalic acid, phthalic acid, succinic acid, tartaric acid, and acetic acid.
[0063] Secondly, the amino acid organic acid includes one or more selected from the group consisting of nitrilotriacetic acid (NTA), iminodiacetic acid (IDA), methyliminodiacetic acid (MIDA), hydroxyethyliminodiacetic acid (HIDA), diethylenetriamine pentaacetic acid (DPTA), ethylenediaminetetraacetic acid (EDTA), N-hydroxyethyl ethylenediaminetetraacetic acid (HEDTA), methylethylenediaminetetraacetic acid (MEDTA), and triethylenetetraaminehexaacetic acid (TTHA).
[0064] The amount of organic acid added may be 0.05 to 5% by weight relative to the weight of the slurry composition, preferably 0.1 to 3% by weight, and most preferably 0.1 to 1% by weight. If the amount is too small, the chelating agent will not show the desired effect of the present invention; if the amount is too large, the chelating agent will be consumed without further effect.
[0065] In a preferred embodiment of the present invention, the antioxidant includes one or more selected from the group consisting of ascorbic acid, L(+)-ascorbic acid, isoascorbic acid, ascorbic acid derivatives, gallic acid, formamidinesulfinic acid, uric acid, tartaric acid, and cysteine. The amount of the antioxidant added relative to the weight of the slurry composition can be 0.05 to 1% by weight, the preferred concentration is 0.1 to 0.5% by weight, and the optimal concentration is 0.2 to 0.3% by weight. If the amount is too small, the antioxidant effect of the metal will not be exhibited; if the amount is too large, the antioxidant will be consumed without further effect, or it will remain on the surface of the wafer and become the cause of defects.
[0066] From the perspective of composition stability, the pH value of the CMP slurry composition according to an embodiment of the present invention is preferably 9 to 12. If the pH value range is less than 9, the aggregation phenomenon of the colloidal silica particles and the removal rate are unstable, and if the pH value range exceeds 12, the removal rate is unstable and therefore poor.
[0067] In order to adjust the pH value to the above range, KOH, NH4OH, NaOH, TMAH, TBAH, KNO3, NH4NO3, etc. can be used alone or in combination as alkaline substances. Since the pH value is closely related to the particle stability and polishing rate of the slurry composition, it must be precisely adjusted.
[0068] In the CMP slurry composition according to an embodiment of the present invention, the solvent is used to adjust the film removal rate by adjusting the concentration of the composition. The solvent may be deionized water, water, etc., but deionized water is preferably used.
[0069] The film to be polished by the slurry composition may further include a copper-containing film.
[0070] Furthermore, the composition of the slurry can adjust a desired polishing rate for a thin film used as a copper-containing film and a barrier film or an oxide film used as a semiconductor insulating film, the thin film including any one selected from the group consisting of titanium (Ti), tantalum (Ta), ruthenium (Ru), molybdenum (Mo), cobalt (Co) or gold (Au). Therefore, the slurry composition can also show an excellent polishing selectivity ratio between the polishing target film and other thin films.
[0071] Hereinafter, the present invention will be described in more detail by way of examples. However, these examples are only for the purpose of illustrating the present invention, and it is obvious to those having ordinary knowledge in the technical field to which the present invention belongs that these examples are not intended to limit the scope of the present invention.
[0072] Best Mode for Carrying Out the Invention
[0073] [Examples 1 to 7 and Comparative Examples 1 and 2]
[0074] Slurry compositions for polishing a copper barrier layer of Examples 1 to 7 and Comparative Examples 1 and 2 were prepared according to the contents listed in Table 1 below.
[0075] Here, the content of colloidal silica was set to 13% by weight, and the particle size of the colloidal silica used was 90 nm. KOH was used as the pH adjuster, and KNO3 was used as the nitride, and the contents were set to 0.5% by weight, respectively. Ascorbic acid was used as the antioxidant, and the contents were set to 0.2% by weight.
[0076] [Table 1]
[0077]
[0078] BTA:Benzotriazole
[0079] IDA: Iminodiacetic acid
[0080] AA: Acetic acid
[0081] ADBS: Ammonium dodecyl benzene sulfonate
[0082] PVP: Polyvinylpyrrolidone
[0083] [Experimental Examples 1 to 7 and Comparative Experimental Examples 1 and 2]
[0084] The polishing rates (Removal Rate) and dishing (Dish) based on the slurry compositions of Examples 1 to 7 and Comparative Examples 1 and 2 were measured respectively. The results of Experimental Examples 1 to 7 and Comparative Examples 1 and 2 are recorded in Table 2 below.
[0085] [Polishing conditions]
[0086] 1. Polishing equipment: 12-inch (300 mm) CMP equipment-AP-300 (CTS)
[0087] 2. Polishing pad: IC1010 (Dow)
[0088] 3. Platen speed: 103 rpm
[0089] 4. Head speed: 97 rpm
[0090] 5. Flow rate: 300 cc / min
[0091] 5. Pressure: 2.2 psi
[0092] Regarding the measurement of the polishing rate, when polishing was performed using a 12-inch (300 mm) CMP equipment, the polishing rates of Cu and Ta were calculated using a four-point probe (CMT-SR 5000, AIT Co., Ltd.).
[0093] For PTEOS as an oxide film (OXIDE), the change in thickness before and after CMP was measured using an Atlas device from Nanometrics to calculate the polishing rate.
[0094] The polishing selectivity ratio was calculated from the polishing rate of each film quality as follows.
[0095] - The polishing selectivity of silicon oxide film (Silicon oxide) to tantalum nitride film (TaN) = polishing rate of silicon oxide film / polishing rate of tantalum nitride film (TaN)
[0096] - Polishing selectivity of copper film (Cu) to tantalum nitride film (TaN) = polishing rate of copper film (Cu) / polishing rate of tantalum nitride film (TaN)
[0097] The dishing measurement was performed by measuring the thickness of each film using a transmission electron microscope (JEM-2000, JEOL) and calculating the thickness as follows.
[0098] - Cu dishing = (Cu edge thickness – Cu center thickness)
[0099] - Ox dishing = (Ox edge thickness -Ox center thickness)
[0100] [Table 2]
[0101]
[0102] The polishing rates, selectivity ratios, and dishing values of Experimental Examples 1 to 7 and Comparative Experimental Examples 1 and 2 described in Table 2 were evaluated as follows.
[0103] First, it can be confirmed that, compared with the conventional comparative examples 1 and 2, in the experimental examples 1 to 7 using complexing agents, the polishing rate of the copper film is significantly increased.
[0104] Second, it can be confirmed that the polishing rate of the silicon oxide film is significantly increased in Experimental Examples 1 to 7 using polyvinyl pyrrolidone (PVP) as a surface protective agent, compared with the conventional Comparative Examples 1 and 2.
[0105] Third, it can be confirmed that in Experimental Examples 1 to 7, the polishing rate of the copper film increases as the content of iminodiacetic acid (IDA) as a complexing agent increases, and the concavity of the copper film layer decreases as the content of ammonium dodecylbenzenesulfonate (ADBS) as a surface protective agent increases.
[0106] For such reasons, the selection ratios of Experimental Examples 1 to 7 are superior to those of Comparative Experimental Examples 1 and 2 in the related art.
[0107] In the case of Comparative Experimental Example 2, the following problem occurred: since the content of benzotriazole (BTA) as an anticorrosive agent was small, although the polishing rate of the copper film layer was improved, dishing increased.
[0108] [Examples 8 to 11 and Comparative Examples 3 to 5]
[0109] Slurry compositions for polishing a copper barrier layer of Examples 8 to 11 and Comparative Examples 3 to 5 were prepared according to the contents described in Table 3. Slurry compositions for polishing a copper barrier layer were prepared according to the particle size of colloidal silica and the content of the surface protective agent ADBS.
[0110] Here, the content of colloidal silica was set to 15 wt %, BTA was used as the heterocyclic compound and was set to 0.05 wt %, AA was used as the organic acid and was set to 0.1 wt %, PVP was used as the surface protective agent and was set to 0.2 wt %, KOH was used as the pH adjuster and was set to 0.2 wt %, and KNO 3 was used as the nitride and was set to 1.0 wt %.
[0111] [Table 3]
[0112]
[0113] [Experimental Examples 8 to 11 and Comparative Experimental Examples 3 to 5]
[0114] The polishing rate (Removal Rate), selectivity, and defect (number of defects) based on the slurry compositions of Examples 8 to 11 and Comparative Examples 3 to 5 were measured respectively, and the results of Experimental Examples 8 to 11 and Comparative Experimental Examples 3 to 5 are recorded in the following Table 4.
[0115] Defect (defect count) measurement was performed using a light source with a spot size of 10 μm using a device with a trade name of [AIT-XP+] manufactured by KLA-Tencor Corporation.
[0116] [Table 4]
[0117]
[0118] In Table 4, the polishing rate increases as the particle size increases, but there is a problem of increased number of defects. In the case of Comparative Experimental Examples 3 and 4 where the particle size is less than 70 nm, the polishing rate of both films decreases significantly, resulting in a delay in the process time, which becomes a problem in terms of productivity.
[0119] Furthermore, it was confirmed that the number of defects decreased as the content of ammonium dodecylbenzenesulfonate (ADBS) as a surface protective agent increased.
[0120] [Examples 12 to 18 and Comparative Examples 6 and 7]
[0121] Slurry compositions for polishing a copper barrier layer of Examples 12 to 18 and Comparative Examples 6 and 7 were prepared according to the contents described in Table 5 below.
[0122] Here, the content of colloidal silica was set to 15% by weight, and the particle size of the colloidal silica used was 90 nm. KOH was used as the pH adjuster, and KNO3 was used as the nitride, and the contents were set to 0.5% by weight, respectively. Ascorbic acid was used as the antioxidant, and the contents were set to 0.2% by weight.
[0123] [Table 5]
[0124]
[0125] BTA:Benzotriazole
[0126] IDA: Iminodiacetic acid
[0127] AA: Acetic acid
[0128] ADBS: Ammonium dodecyl benzene sulfonate
[0129] PVP: Polyvinylpyrrolidone
[0130] [Experimental Examples 12 to 18 and Comparative Experimental Examples 6 and 7]
[0131] The polishing rate (Removal Rate), selectivity, and dishing based on the slurry compositions of Examples 12 to 18 and Comparative Examples 6 and 7 were measured respectively, and the results of Experimental Examples 12 to 18 and Comparative Examples 6 and 7 are recorded in Table 6 below.
[0132] [Table 6]
[0133]
[0134] The polishing rates, selectivity ratios, and dishing values of Experimental Examples 12 to 18 and Comparative Experimental Examples 6 and 7 described in Table 6 were evaluated as follows.
[0135] First, it can be confirmed that, compared with the conventional comparative experimental examples 6 and 7, in the experimental examples 12 to 18 using complexing agents, the polishing rate of the copper film is significantly increased.
[0136] Second, it can be confirmed that the polishing rate of the silicon oxide film is significantly increased in Experimental Examples 12 to 18 using polyvinyl pyrrolidone (PVP) as a surface protective agent, compared with the conventional Comparative Experimental Examples 6 and 7.
[0137] Third, it can be confirmed that in Experimental Examples 12 to 18, the polishing rate of the copper film increases as the content of iminodiacetic acid (IDA) as a complexing agent increases, and the concavity of the copper film layer decreases as the content of ammonium dodecylbenzenesulfonate (ADBS) as a surface protective agent increases.
[0138] For such reasons, the selection ratios of Experimental Examples 12 to 18 are superior to those of Comparative Experimental Examples 6 and 7 in the related art.
[0139] In the case of Comparative Experimental Example 7, since the content of benzotriazole (BTA) as an anticorrosive agent is small, although the polishing rate of the copper film layer is improved, dishing increases.
[0140] [Examples 19 to 22 and Comparative Examples 8 to 10]
[0141] Slurry compositions for polishing a copper barrier layer of Examples 19 to 22 and Comparative Examples 8 to 10 were prepared according to the contents listed in Table 7 below.
[0142] A slurry composition for polishing a copper barrier layer was prepared according to the particle size of colloidal silica and the content of the surface protecting agent ADBS used in Table 7 below.
[0143] Here, the content of colloidal silica was set to 15 wt %, BTA was used as the heterocyclic compound and was set to 0.05 wt %, AA was used as the organic acid and was set to 0.1 wt %, PVP was used as the surface protective agent and was set to 0.2 wt %, KOH was used as the pH adjuster and was set to 0.2 wt %, and KNO 3 was used as the nitride and was set to 1.0 wt %.
[0144] [Table 7]
[0145]
[0146] [Experimental Examples 19 to 22 and Comparative Experimental Examples 8 to 10]
[0147] The polishing rates (Removal Rate) and defects (number of defects) based on the slurry compositions of Examples 19 to 22 and Comparative Examples 8 to 10 were measured respectively, and the results of Experimental Examples 19 to 22 and Comparative Examples 8 to 10 are recorded in Table 8 below.
[0148] Defect (defect count) measurement was performed using a light source with a spot size of 10 μm using a device with a trade name of [AIT-XP+] manufactured by KLA-Tencor Corporation.
[0149] [Table 8]
[0150]
[0151] The polishing rates, selectivity ratios, and defect values of Experimental Examples 19 to 22 and Comparative Experimental Examples 8 to 10 described in Table 8 were evaluated as follows.
[0152] That is, as the particle size of colloidal silica increases, the polishing rate increases, but there is a problem of increased number of defects. In the case of Comparative Experimental Examples 8 and 9 where the particle size is 70 nm or less, the polishing rate of both films decreases significantly, resulting in a delay in the process time, which becomes a problem in terms of productivity.
[0153] Furthermore, it was confirmed that the number of defects decreased as the content of ammonium dodecylbenzenesulfonate (ADBS) as a surface protective agent increased.
[0154] When the colloidal silica content was 13% and 15%, the results showed the same tendency, and reproducibility was ensured.
[0155] As described above, the present invention is described by limited embodiments, but the present invention is not limited to the embodiments, and those skilled in the art can make various modifications and changes based on such descriptions. Therefore, the scope of the present invention shall not be limited by the described embodiments, and in addition to being defined by the scope of the claims described below, it shall also be defined by parts that are equivalent to the scope of the claims.
Claims
1. A CMP slurry composition for polishing a copper barrier layer, comprising: Abrasive particles; Heterocyclic compounds; Nitride; Organic acid; Surface protective agent; Antioxidant; pH adjuster; and the balance deionized water.
2. The CMP slurry composition for polishing a copper barrier layer according to claim 1, wherein: The abrasive particles include colloidal silica in which nanometer-sized silica particles are stably dispersed in a solvent without sedimentation.
3. The CMP slurry composition for polishing a copper barrier layer according to claim 2, wherein: The abrasive particles are present in the slurry composition in an amount of 13 to 15 wt %.
4. The CMP slurry composition for polishing a copper barrier layer according to claim 3, wherein: The abrasive particles have a particle size of 75 to 95 nm.
5. The CMP slurry composition for polishing a copper barrier layer according to claim 1, wherein: The heterocyclic compound has two or more nitrogen atoms and includes one or more selected from the group consisting of 1,2,4-H-triazole, 5-methylbenzotriazole, tetrazole, imidazole, 1,2-dimethylimidazole, benzotriazole (BTA), 1H-benzotriazole acetonitrile, and piperidine.
6. The CMP slurry composition for polishing a copper barrier layer according to claim 1, wherein: The nitride includes one or more selected from the group consisting of potassium nitrate (KNO3), nitric acid (HNO3), ammonium nitrate (NH4NO3), iron nitrate (Fe(NO3)2), and copper nitrate (Cu(NO3)2).
7. The CMP slurry composition for polishing a copper barrier layer according to claim 6, wherein: The nitride is present in the slurry composition in an amount of 0.1 to 10 wt %.
8. The CMP slurry composition for polishing a copper barrier layer according to claim 1, wherein: The organic acids include: i) one or more carboxylic acid organic acids selected from the group consisting of citric acid, glutaric acid, malic acid, maleic acid, oxalic acid, phthalic acid, succinic acid, tartaric acid, and acetic acid; and ii) one or more amino acid organic acids selected from the group consisting of nitrilotriacetic acid (NTA), iminodiacetic acid (IDA), methyliminodiacetic acid (MIDA), hydroxyethyliminodiacetic acid (HIDA), diethylenetriaminepentaacetic acid (DPTA), ethylenediaminetetraacetic acid (EDTA), N-hydroxyethylethylenediaminetetraacetic acid (HEDTA), methylethylenediaminetetraacetic acid (MEDTA) and triethylenetetraaminehexaacetic acid (TTHA).
9. The CMP slurry composition for polishing a copper barrier layer according to claim 8, wherein: The organic acid is present in the slurry composition in an amount of 0.1 to 3 wt %.
10. The CMP slurry composition for polishing a copper barrier layer according to claim 1, wherein: The surface protective agent includes: one or more nonionic surface protective agents selected from the group consisting of polyvinyl alcohol (PVA), ethylene glycol (EG), glycerol, polyethylene glycol (PEG), polypropylene glycol (PPG), and polyvinyl pyrrolidone (PVP); and one or more anionic surface protective agents selected from the group consisting of ammonium dodecyl benzene sulfonate, ammonium polyoxyethylene alkyl sulfonate, and ammonium polyoxyethylene alkyl aryl sulfonate.
11. The CMP slurry composition for polishing a copper barrier layer according to claim 10, wherein: The surface protective agent is present in the slurry composition in an amount of 0.3-0.8 wt %.
12. The CMP slurry composition for polishing a copper barrier layer according to claim 1, wherein: The antioxidant includes at least one selected from the group consisting of ascorbic acid, L(+)-ascorbic acid, isoascorbic acid, ascorbic acid derivatives, gallic acid, formamidinesulfinic acid, uric acid, tartaric acid, and cysteine.
13. The CMP slurry composition for polishing a copper barrier layer according to claim 12, wherein: The antioxidant is present in the slurry composition in an amount of 0.1 to 0.5 wt %.
14. The CMP slurry composition for polishing a copper barrier layer according to claim 1, wherein: The pH adjuster includes at least one selected from the group consisting of KOH, NH4OH, NaOH, TMAH, TBAH and HNO3.
15. The CMP slurry composition for polishing a copper barrier layer according to claim 14, wherein: The slurry composition has a pH value of 9 to 12.
16. The CMP slurry composition for polishing a copper barrier layer according to claim 1, wherein: The polishing target film of the slurry composition includes: a thin film used as a copper-containing film and a barrier film or an oxide film used as a semiconductor insulating film, and the thin film includes any one selected from the group consisting of titanium (Ti), tantalum (Ta), ruthenium (Ru), molybdenum (Mo), cobalt (Co) and gold (Au).
17. The CMP slurry composition for polishing a copper barrier layer according to claim 16, wherein: The CMP slurry composition has a polishing selectivity ratio of 1:1-4:0.5-1 for tantalum nitride film (TaN), silicon oxide film (Silicon oxide), and copper film (Cu).
Citation Information
Patent Citations
CMP slurry composition for polishing copper barrier layer and polishing method using the same
KR101465604B1
Slurry composition for polishing copper barrier layer
KR101548715B1
Barrier chemical mechanical planarization composition and method of use thereof
KR101698490B1
Slurry composition for polishing a copper barrier layer
KR1020210095548A